A large scale multicentre randomized, placebo-controlled subcutaneous house dust mite allergen immunotherapy (HDM SCIT) in allergic rhinitis: MITAR Study - Suratannon, Narissara; Limsuwan, Ticha; Tantilipikorn, Pongsakorn; Chatchatee, Pantipa; Saengapaswiriya, Atik; Boonpiyathad, Tadech; Thongngarm, Torpong; Roongpuvapaht, Boonsam; Chantaphakul, Hiroshi; Kulalert, Prapasri; Thanaviratananich, Sanguansak; Sangsupawanich, Pasuree; et al. (Asian Pacific journal of allergy and immunology, 2024)
Previous house dust mite subcutaneous immunotherapy (HDM SCIT) placebo-controlled trials have small sample sizes and lack a consensus on baseline treatment. To determine the efficacy of HDM SCIT in moderate-to-severe allergic rhinitis (AR) patients treated with an intranasal corticosteroid at baseline. We conducted a randomized, placebo-controlled trial comparing HDM SCIT against placebo in Dermatophagoides pteronyssinus (Der p) sensitized. All patients received standard of care according to Allergic Rhinitis and its Impact on Asthma (ARIA) guideline, including an intranasal steroid (INCS) at baseline. The primary endpoint was the comparison of a composite score, combining the total nasal symptom score and medication score, assessed at the twelfth month post-treatment. Of the 144 subjects, 108 received HDM-SCIT and 36 received a placebo. The median age was 30 years (range 11-61), with 60% being female. The mean Der p wheal diameter was 9.4 mm (SD 4.4). After one year of treatment, the composite score median (IQR) in the HDM SCIT group and the placebo group was 0.75 (0.50-1.13) and 0.63 (0.50-1.25), respectively (p > 0.05). Both groups exhibited a significant mean change in the composite score from baseline (p < 0.001), but there was no significant difference between the groups. The median (IQR) serum Der p-specific immunoglobulin G4 level significantly increased only in the HDM SCIT arm (p ≤ 0.001). One-year HDM SCIT significantly reduced both symptoms and medication use in HDM-allergic rhinitis patients. However, the changes were not significantly different from those in the placebo group, who also received an INCS at baseline. A longer-term study is warranted to assess disease modification factors.